(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Teenage pregnancy is a major public health issue these days and is associated with adverse maternal and fetal outcomes. This study was conducted to determine the adverse maternal and fetal outcomes in teenage pregnancy. MATERIALS AND METHODS: This was a hospital based descriptive cross-sectional study. All the teenage pregnant women (15-19 years of age) with a singleton pregnancy coming to antenatal ward of Birat Medical College Teaching Hospital from 22nd December 2022 to 21th December 2023 were enrolled in the study, irrespective of their APGAR score at birth, NICU admission and early neonatal death and intrauterine fetal death were noted after delivery. RESULTS: The incidence of teenage pregnancy was 1.7%, and the mean age was 18.36±.83 years. Majority (53.3 %) of the women had normal vaginal delivery. The most common maternal complication was preterm labor (26.7%), while the most common fetal complication was low birth weight (38.7%). 29.3% were admitted to NICU, 25.3% had low APGAR score, 2.7% had stillbirth, 1.3% had early neonatal death. CONCLUSION: Teenage pregnancy was associated with a high rate of adverse maternal and fetal outcomes like premature delivery, anemia, pregnancy induced hypertension, instrumental deliveries, lower segment cesarean section (LSCS), low birth weight, low APGAR score at birth and NICU admission.